Job Change and the Middle Seasons of a Man's Life - Hill, Raymond E.; Miller, Edwin L. (Academy of Management Journal, 1981)
Developmental tasks faced by adults in midlife were found to be related to various criteria in job changing decisions. The establishment period of adulthood as well as the midlife transition were particularly strong influences. These results are discussed from the standpoint of adult development and human resource management.